The relationship between psychological empowerment and job burnout: a model with a mediating role of self-efficacy in nurses - Yazdanparast , Sedigheh; Manzari Tavakoli, Hamdollah; Sayadi , Saeed; Shokooh, Zahra; Salajegheh , Sanjar (Social Determinants of Health, 2022)
Background: The present study aimed to investigate the relationship between psychological empowerment and job burnout with a mediating role of self-efficacy in nurses of private hospitals in Shiraz. Methods: The present study was applied in terms of aim. The statistical population included nurses of private hospitals in Shiraz. According to the statistics of the Deputy of Shiraz University, their number was 750 people. Using Cochran's formula, the sample size was determined at 256 people. To collect data, Maslach job burnout questionnaire, Spreitzer psychological empowerment questionnaire and Sherer & Adams self-efficacy questionnaire and structural equation method were used to analyze the data. Results: The absolute value of the path coefficient to explain the relationship between psychological empowerment and job burnout was -0.545 and t-statistic is higher than 1.96. There was a negative relationship between psychological empowerment and job burnout. Also, psychological empowerment with a mediating role of self-efficacy has a negative path coefficient was -0.704 and t-statistic is higher than 1.96. Self-efficacy increased the effect of psychological empowerment on job burnout. Conclusion: Since perfectionist people and those extremely involved at work suffer from job burnout emotionally and self-efficacy relationship in line with psychological empowerment and inverse relationship with job burnout, it is necessary to take special measures for psychological empowerment to prevent job burnout by managers to increase the efficiency of nurses.